Design and analysis of collision free MAC for wireless sensor networks with or without data retransmission. (15th February 2017) - Sahoo, Prasan Kumar; Sheu, Jang-Ping
Abstract: In this paper, a new communication mechanism for IEEE 802.15.4 based Wireless Sensor Networks (WSNs) is designed to reduce the collisions and to prevent simultaneous data transmission by the nodes. Analytical models are designed for the uplink traffic in beacon-enabled slotted CSMA/CA with acknowledgements. In order to avoid the collisions and thereby the number of retransmissions, a new medium access control (MAC) protocol is designed. Beside, the current mechanism of IEEE 802.15.4 CSMA/CA is extended to develop the analytical models by including retransmission limits of the nodes with packet collision probability. Taking uplink traffic of the sensors, a Markov chain model is developed to analyze the energy consumption and throughput of the nodes and to study the impact of various network parameters such as the data rate, packet size and node numbers. The proposed models show that the throughput of the system is reduced and energy consumption is increased due to data retransmissions irrespective of the data rates.